Evaluation of drug poisoning cases in pediatric emergency department - Kutluturk, Kazim; Aslan, Mehmet (Annals of Medical Research, 2021)
Aim: This study aims to examine the demographic and clinical characteristics of childhood drug poisoning, review changes in diagnostic methods and treatments and identify factors affecting mortality to ultimately determine the present clinical picture. In doing so, more insight can be provided on the diagnosis, treatment, and prevention of poisonings. Materials and Methods: The retrospective evaluation of 655 patients between ages 1 month-18 years who were admitted to the Pediatric Emergency Department of Turgut Ozal Medical Center between January 2009 and June 2016 with cases of drug poisoning (mean 44±18 months). Results: Four hundred and nine female (62.4%) and 246 male patients (37.6%) were evaluated for a total of 655 cases. Drug poisoning cases were found to account for 1.08% of all visits to the emergency department. It was discovered that 62.1% of the poisonings were accidental, whereas 33% were suicide attempts and 4.9% therapeutic mistakes. 94.8% of drug poisonings occurred at households, while 5.2% occurred in non-household environments. Drug poisonings presented differences in terms of gender (62.4% female, 37.6% male). The number of drug poisoning cases were found to be higher in the months of summer and spring. The number of female cases peaked in the 13-18 age group (211 cases) and were higher than the same age group of males (30 cases). Conclusions: In our present study, we highlighted the profile of pediatric drug poisoning cases admitted to the Pediatric Emergency Service.